The progress of earthquake risk reduction and recovery in Turkey: From Marmara to Van - Varol, Asaf; Enia, Jason (Global Risk Forum (GRF), 2016)
Since 1939, there have been several important earthquakes in Turkey. However, from the Erzincan quake in 1939 through the Marmara quake in 1999 and then the Van quake in 2011, the number of people dying in earthquakes has steadily decreased. In the 1999 Marmara earthquake, more than 17000 people were killed and a great deal of regional infrastructure was destroyed. Almost 12 years after the Marmara earthquake there were many fewer deaths in a similar magnitude earthquake in Van. What had changed in Turkey during this time? This paper compares these two earthquakes and reveals big differences in terms of preparedness, mitigation, and response. The sources of these changes are explained, focusing on institutional changes regarding Turkey's disaster risk reduction system as well as urban transformations in Ankara and Van. © 2016 CURRAN-CONFERENCE. All rights reserved.
6th International Disaster and Risk Conference: Integrative Risk Management - Towards Resilient Cities, IDRC Davos 2016 -- 28 August 2016 through 1 September 2016 -- Davos -- 140013
Keywords: Mitigation and preparedness; Recovery; Response; The Marmara earthquake; The Van Earthquake